Assessing the performance of community pharmacies in iran by measuring responsiveness to non-medical needs: An application of who responsiveness framework - Saba Afifi; Amir Hossein Alizadeh Bahmani; Leila Zarei; Motahareh Mahi-Birjand; Mehdi Hoorang; Marziyeh Zare; Iman Karimzadeh; Farzad Peiravian; Mahtabalsadat Mirjalili; Payam Peymani (Wolters Kluwer Medknow Publications, 2021)
Objective: Despite growing debates about the health systems' nonmedical performance, there has not been any empirical research on nonmedical performance and patients' rights consideration as a driver of human rights in the pharmaceutical sector. This study's main objective was to assess the nonmedical performance of community pharmacies of Shiraz, Iran. Methods: A cross-sectional study was conducted using two self-administrated Likert-based questionnaires based on the World Health Organization (WHO) responsiveness framework and the legal charter communicated by the Ministry of Health and Medical Education of Iran. The population was patients older than 18 years who took a prescription from community pharmacies located in Shiraz and willing to answer the questions voluntarily, from 2018 to 2019. Considering the weights of subdimensions of responsiveness provided by the WHO framework, the total score of responsiveness was calculated ranging from 0 to 100. Findings: The response rate was 80.5%. The mean (standard deviation) overall score of responsiveness was 57.18 (21.61), with a median of 56.71. The mean score of client orientation was lower in respondents with a high education level than those with a diploma and under diploma (P = 0.028). Conclusion: Nonmedical pharmacy performance was considered either medium or high in more than half of the cases based on the participants' views. Regarding client, orientation was seen less often in patients with high education level compared to those with a lower education level.